The Bibliometric Analysis of the Sustainable Influence of Physical Education for University Students - Xu, Dekai; Zheng, Yingying; Jia, Yunli (Frontiers in Psychology, 2021)
With the awakening of people’s health consciousness, the concept and practice of health promotion has become the main target of health policies in countries around the world. Therefore, this paper studies the relationship between physical education and health promotion. This paper selects art students from a university in Taoyuan for research and 320 questionnaires are issued. The invalid and incomplete questionnaires are eliminated, obtaining a total of 227 valid questionnaires. Finally, the LISREL (Linear Structural Relations) model is used to analyze the correlation between various factors and health promotion. The results of the model analysis show that in terms of basic fit, the three factors of physical education (course design, teaching content, activity design) have a high correlation to the influence of physical education, reaching a significant level (t> 1.96, p <0.05). In terms of influence on sports participation, the three factors (physiological factors, psychological factors, social factors) of sports participation have reached a significant level (t> 1.96, p <0.05). The two factors of health promotion (physiological health, mental health, practical ideas) have a high correlation to the influence of health promotion, reaching a significant level (t> 1.96, p <0.05). There is a positive correlation between physical education, sports participation and health promotion. Participating in physical activities can improve the body’s immune function, reduce the symptoms of chronic diseases, and have a positive effect on promoting health.